MEMBANGUN JARINGAN KOMUNIKASI PESANTREN SALAFIYAH: DARI LISAN KE MEDIA SOSIAL - Ikhsan Ahmad; Iman Mukhroman; Rangga Galura Gumelar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
As an educational institution, salafiyah pesantren face problems in adopting modern digital communication systems. The purpose of this community service is to assist salafiyah pesantren in building an effective communication system by using social media as a substitute for the traditional method of delivering information verbally. The methods used are mentoring, training, and implementation of communication technology. The program was implemented at Salafiyah Al-Fathaniyah Islamic Boarding School located in Serang City, Banten. The results showed that the effectiveness of communication outreach, dissemination of information about activities, and participation of alumni and communities around the pesantren increased significantly. The program is able to preserve the sociocultural identity and traditions of the pesantren while still using modern communication tools, so that the essence of salafiyah is not lost. The positive impacts include an increase in the transparency of pesantren management, more efficient coordination of activities, and the expansion of a wider da'wah network.